2020
DOI: 10.1155/2020/1592910
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Grade 2-3 Endo-Periodontal Lesions Treated Nonsurgically in Patients with Periodontitis: A Retrospective Case-Control Study

Abstract: Background. Endo-periodontal lesions are bacterial infectious diseases involving both the periodontal and pulp tissues with poor outcomes. It is hard for clinicians to predict their prognosis. The aim of this study is to investigate the factors affecting the prognosis of endo-periodontal lesions. Methods. A total of 140 teeth diagnosed with grade 2-3 endo-periodontal lesions in patients with periodontitis were recruited in this study. They were divided into high and low responder groups, according to the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Endo-periodontal lesions (EPLs) are bacterial infectious diseases that together affect periodontal and endodontic tissues of the same tooth, with periodontal tissue damage and pulp inflammation/necrosis, defined by a pathological communication between the pulpal and periodontal tissues [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endo-periodontal lesions (EPLs) are bacterial infectious diseases that together affect periodontal and endodontic tissues of the same tooth, with periodontal tissue damage and pulp inflammation/necrosis, defined by a pathological communication between the pulpal and periodontal tissues [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common signs and symptoms associated with a tooth affected by EPLs are deep periodontal pockets reaching or close to the apex with a periodontal probing depth (PD) of ≥5 mm and a clinical attachment level (CAL) of ≥3 mm, and a negative or altered response to pulp vitality tests, including spontaneous pain history [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the combined lesions a periodontal treatment is also important to influence the secondary periodontal disease, because of the communication between the endodontic and periodontal processes, the use of therapeutic drugs is essential to kill any bacteria and to stimulate tissue repair. [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that periodontitis could induce various complications, including periodontal abscess, pulp lesions, furcation lesion, as well as mucosal thickening [16][17][18]. First of all, the special anatomical structures, including the apical foramen, the lateral and accessory canals, and the dentinal tubules, form an intimate continuum between the periodontal and endodontic tissues, through which pathological changes of either may lead to infection of the other [30,31]. These ndings indicate the communication between the periodontal and endodontic tissues and pulp lesions could be induced by periodontitis.…”
Section: Discussionmentioning
confidence: 99%